1994
DOI: 10.1093/carcin/15.9.1979
|View full text |Cite
|
Sign up to set email alerts
|

In vitro carcinogenesis of hamster pancreatic duct cells: cellular and molecular alterations

Abstract: Neoplastic transformation of Syrian golden hamster (SGH) pancreatic duct cells was induced by in vitro treatment with the direct-acting carcinogens N-methylnitrosourea (MNU) and N-(2-hydroxypropyl)nitrosourea (HPNU), with subsequent selection by sustained culture in serum- and epidermal growth factor (EGF)-deprived medium. The present study examines the efficacy of serum and EGF deprivation as a selection pressure and the effect of the carcinogen dose, frequency and interval of exposure on tumorigenesis and K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Moreover, according to our experience the growth of cells deriving from islets is significantly different from that of cultured ductal cells, in that ductal cells form glandular structures even in monolayer (27). Because it has been shown that BOP can transform hamster ductal cells in vitro (20,21), it was of interest to examine the effect of BOP on isolated pure islets in vitro in the system we have established (19). In this system, isolation and long-term maintenance of pure islets free of exocrine cell contamination was possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, according to our experience the growth of cells deriving from islets is significantly different from that of cultured ductal cells, in that ductal cells form glandular structures even in monolayer (27). Because it has been shown that BOP can transform hamster ductal cells in vitro (20,21), it was of interest to examine the effect of BOP on isolated pure islets in vitro in the system we have established (19). In this system, isolation and long-term maintenance of pure islets free of exocrine cell contamination was possible.…”
Section: Discussionmentioning
confidence: 99%
“…The number of viable cells, determined by the dye exclusion test, was counted at 24 h intervals using a hemocytometer. Population doubling time was calculated by plotting the mean cell number versus days in culture on a semi-logarithmic graph, as reported (21,22).…”
Section: Cell Growth Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…10 We and others have shown that in vitro treatment of hamster ductal cells with pancreatic carcinogens leads to malignant cell transformation and adenocarcinoma in vivo. 5,6 No giant cell carcinomas have ever been produced. On the contrary, treatment of isolated and purified hamster islets with BOP produced tumors of giant cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of isolated hamster pancreatic ductal cells with BOP or methylnitrosourea (MNU) in vitro resulted in the induction of anaplastic cancer, but no giant cell tumors have been observed. 5,6 A similar treatment scheme of isolated purified hamster pancreatic islets with BOP, however, resulted in formation of anaplastic invasive cancers, which, in vitro and in vivo, presented patterns consistent with human pancreatic giant cell tumor. In this report we describe some biological patterns of this tumor compared to the human tumor.…”
mentioning
confidence: 96%